Assessment of the Performance and Exhaust Emission of a Diesel Engine Using Water Emulsion Fuel (WEF) in Different Engine Speed and Load Conditions - Seyed Saeed Hoseini; Mohammad Amin Sobati (Journal of Renewable Energy and Environment, 2021)
The performance characteristics and exhaust emission of a diesel engine using Water Emulsion Fuel (WEF) have been investigated under different engine speeds (1600 to 2400 rpm) and load conditions (25 to 100 %). The experiments were carried out on an air-cooled diesel engine of single cylinder using the WEF containing 5 % water, 2 % surfactant with Hydrophilic-Lipophilic Balance (HLB) of 6.8. The engine performance and exhaust emission using WEF were also compared with the Neat Diesel Fuel (NDF). According to the results, average reduction of 9.7 % in the engine torque and brake power was observed using WEF at all engine speeds. In addition, a 7.9 % increase in the Brake Specific Fuel Consumption (BSFC) and a 3.7 % increase in the Brake Thermal Efficiency (BTE) were observed for WEF in comparison with NDF in all loading conditions. In case of emission, significant lower hydrocarbon emission (i.e., 14.6 % on average) was observed for WEF comparing to NDF at all engine speeds. Moreover, a considerable reduction in the NOx emission (i.e., 31.1 % on average) was observed for the WEF comparing to the NDF in every engine load. In summary, the application of WEF leads to the reduction in the emission of different pollutants with a positive impact on the environment.